Tdkp/AQUA: Unified modeling of electroluminescence in nanostructures - Steiger, Sebastian; Veprek, Ratko G.; Witzigmann, Bernd (Optical and Quantum Electronics, 2009)
This article summarizes the capabilities of the optoelectronic simulation framework tdkp/AQUA aimed at the description of electroluminescence in semiconductor nanostructures such as light-emitting diodes. tdkp is a stand-alone finite-element software able to accurately calculate strain, built-in fields due to spontaneous and piezoelectric polarization, bound quantum states using k · p theory, gain and luminescence spectra in zero-to three-dimensional structures. AQUA calculates transport through nanostructures using a model which accounts for the distinct behaviour of carriers confined to active regions and unconfined carriers. Furthermore, it computes electroluminescence spectra via a self-consistent coupling of the confined carriers to quantum-mechanical calculations using tdkp. Two examples are presented which highlight the versatility and generality of the developed framework. © Springer Science+Business Media, LLC. 2010.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Device simulation; Drift-diffusion; Electroluminescence; Kp theory; LED